PENGEMBANGAN PRODUK EKONOMI KREATIF KAIN SASIRANGAN DAN PENERAPAN STRATEGI KOMUNIKASI PEMASARAN TERPADU DALAM MENINGKATKAN DAYA TARIK KOTA BANJARMASIN SEBAGAI DESTINASI PARIWISATA - kasypul Anwar kasypul; Gt. Irhamni Gt. Irhamni (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Abstract: The objectives of this research are (1) To find out, study and analyze the development of creative economy products in Sasirangan fabric in the city of Banjarmasin. (2) To find out, study and analyze the application of integrated marketing communication strategies in Sasirangan fabric creative economy products in Banjarmasin City. (3) To find out, study and analyze the attractiveness of the city of Banjarmasin as a tourism destination from the perspective of tourists. (4) To find out, study and analyze how much influence the sasirangan fabric creative economic product development and the application of integrated marketing communication strategies to the attractiveness of Banjarmasin City as a tourism destination. This study uses an explanatory survey method, because it will explain the relationship between the variables studied. While the type of relationship between variables used in this study is causality, that is, the independent variable / independent variable influences the dependent variable / dependent variable. the results showed that in general the integrated marketing communication strategy in the creative economy products in the City of Banjarmasin had been implemented well. This can be seen from the majority of respondents' answers that stated agreed with the questions asked. But of the four factors forming integrated marketing communication, aspects of public relations and publicity and advertising are the forming factors that have the most powerful role and have been implemented quite well. This means that as a whole the management of tourism and the creative economy tourism industry has conducted a series of promotions to introduce what is owned by all prospective tourists through various media. Keywords: Product, Strategy, Marketing, Competitiveness.